Implementasi Strategi Pembelajaran Menulis Berbasis Multiple Intelligences - Suniyah Suniyah; Muhammad Rohmadi; Edy Tri Sulistiyo (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2018)
Abstract: The study aims to describe the implementation of learning strategies based on multiple intelligences at SD Islamic International School PSM Magetan. This research is a qualitative descriptive study in the form of a case study. The data in this study are places and events, informants, and documents. The sampling technique used was purposive sampling and snowball sampling. First results show that the learning planning process based on multiple intelligences at the Islamic International School Elementary School PSM Magetan runs well in the form of implementing Multiple Intelligence Research (MIR) preparation of AP, IP, SOW, LP, and authentic assessment instruments. Second results show that the teacher integrates various methods with the types of multiple intelligences of students in writing learning, with authentic assessment. Constraints faced by teachers and schools in the implementation of writing learning strategies based on multiple intelligences can be addressed properly. Keywords: multiple intelligences, learning strategies, writing skills Abstrak: Penelitian bertujuan mendeskripsikan implementasi strategi pembelajaran menulis berbasis multiple intelligences di SD Islamic International School PSM Magetan. Penelitian ini merupakan penelitian deskriptif kualitatif dalam bentuk studi kasus. Data dalam penelitian ini adalah tempat dan peristiwa, informan, dan dokumen. Teknik cuplikan yang digunakan purposive sampling dan snowball sampling. Hasil: (1) proses perencanaan pembelajaran menulis berbasis multiple intelligences di SD Islamic International School PSM Magetan berjalan dengan baik berupa pelaksanaan MultipleIintelligences Research (MIR) penyusunan dokumen AP, IP, SOW, LP, dan instrumen penilaian autentik. (2) guru mengintegrasikan berbagai berbagai metode dengan jenis-jenis kecerdasan majemuk siswa di dalam pembelajaran menulis, dengan penilaian autentik. Kendala yang dihadapi guru dan sekolah dalam implementasi strategi pembelajaran menulis berbasis multiple intelligences dapat diatasi dengan baik.